Problem-Based Learning on Students' Attitude Towards Science: An Action Research - Weni Rahmadani; Nanang Winarno; Siti Sriyati; Titin Supriyatin (ASEAN Journal of Science and Engineering Education, 2024)
Students' attitudes towards science learning based on the results of the questionnaire are still lacking, students' attitudes towards science are lacking because learning is not related to students' everyday problems, learning activities are less fun and students are afraid to express opinions, and students find science learning difficult. This study aims to improve students' attitudes toward science learning on the respiratory system material and wave material using the Problem-Based Learning (PBL) model. The subjects were 32 students (14 males and 18 females). The type of research used in this research is classroom action research (CAR) with 2 cycles. Data collection was carried out by filling out questionnaires and observing attitudes toward science. Attitude toward science indicators consists of 5 indicators, namely: Attitude, Unfavorable outlook, Control beliefs, Behavioral beliefs, and Intention. Based on the results, there was an increase in student attitudes starting from cycles 1 to 2. The student attitudes toward science learning were 69.69 to 71.73%. The average student attitude in one class rose by 2.06%. Attitude toward science in cycles 1 and 2 by applying the PBL model has increased learning outcomes.